Strategi Pemasaran Digital untuk Menarik Wisatawan Milenial ke Hotel Santika Premiere ICE BSD City - Santoso, Yudi; Suwarta, Firdaus (Journal of Information System, Applied, Management, Accounting and Research, 2026)
This study analyzes digital marketing strategies to attract millennial tourists (aged 25–40) to Hotel Santika Premiere ICE BSD City, with reference to trends in 2024–2025. The background of the study is driven by the dominance of millennials in the domestic tourism market (72% rely on digital recommendations) and the urgency of digital transformation in the post-pandemic era. A descriptive qualitative method with a case study approach was employed. Data collection techniques included in-depth interviews (five informants: marketing manager, social media staff, and millennial guests), participatory observation, and document analysis. The results indicate that the MySantika application plays a key role in increasing direct bookings by 30%, supported by three critical features. First, Exclusive Discounts (25% higher interest compared to OTAs), utilized through Ramadan promotions (10% discount and free breakfast). Second, Digital Check-in/Check-out (15% guest satisfaction), which saves approximately five minutes of queuing time through OTP verification and integration with the Property Management System (PMS). Third, Machine Learning–based Personalized Recommendations (20% conversion rate), which tailor room preferences and nearby activities to individual users. Supporting strategies include optimization of Instagram visual content (Reels/Stories generating 40% engagement), collaboration with local influencers (e.g., *Santai Sore Ramadhan* live sessions), and integration of digital payment methods (OVO, QRIS, and PayLater). The main challenges identified are the limited features of the MySantika application for the international market and dependence on internet connectivity. Recommended solutions include the expansion of a global loyalty program and the development of an offline mode feature. The study concludes that the combination of mobile applications, interactive content, and personalization constitutes an effective strategy for reaching millennial tourists. The practical implications emphasize the need for continuous technology-based innovation to sustain growth in the digital era.